SWAT-MODFLOW Model for Groundwater Recharge Variation Assessment: Lower Zab River Basin, Northeastern Iraq - Rahem, Mohammed Jalel; Ruqayah Mohammed (International Journal of Computational and Experimental Science and Engineering, 2025)
For surface and groundwater simulations, recharge is a fundamental water balance unit. Yet, measuring its regional spatiotemporal variation poses a substantial challenge. Mathematical and empirical simulation are the most frequently used approaches at the basin scales. However, the accuracy and dependability of integrated models may be limited due to the limitless number of unknowns and uncertainties they contain. In the Lesser Zab River Basin, A QSWATMOD variant was suggested for evaluating groundwater recharge in northeastern Iraq. The paired version was calibrated using a hydraulic head and daily circulating drift. In comparison to the SWAT version, the QSWATMOD version performed well throughout the flow drift simulation. The results of the study verified that during the predicted period, the watershed saw significant fluctuations in groundwater recharge. The wet season is when a significant amount of recharge takes place. It makes a significant contribution to the region’s average yearly precipitation. The water stability components were assessed locally, and the direct waft additives (lateral and surface) demonstrated significant contributions. All things considered, the QSWATMOD model predicted groundwater recharge in the study area with a respectable degree of accuracy.